2020
DOI: 10.3390/jcm9072293
|View full text |Cite
|
Sign up to set email alerts
|

Bone Morphogenetic Protein (BMP)4 But Not BMP2 Disrupts the Barrier Integrity of Retinal Pigment Epithelia and Induces Their Migration: A Potential Role in Neovascular Age-Related Macular Degeneration

Abstract: Disruption of retinal pigment epithelial (RPE) barrier integrity and RPE migration are hallmark features in neovascular age-related macular degeneration (nAMD), but the underlying causes and pathophysiology are not completely well-defined. Herein, we aimed to evaluate the effect of bone morphogenetic proteins (BMPs) on the barrier function and migration of RPE. In particular, we investigated the role of BMP2 and BMP4 in these processes as our analysis of RNA-sequencing (seq) data from human donor eyes demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 58 publications
1
14
0
Order By: Relevance
“…A2E-treated cells showed dysregulated expression of genes clustered within nectin, focal adhesion kinase, E-cadherin and N-cadherin adhesion pathways. Our results deal with those recently reported by Ibrahim et al [ 49 ]. The authors observed the disruption of the RPE barrier due to increased MMP2 metalloproteinase activity, following high BMP4 concentration.…”
Section: Discussionsupporting
confidence: 93%
“…A2E-treated cells showed dysregulated expression of genes clustered within nectin, focal adhesion kinase, E-cadherin and N-cadherin adhesion pathways. Our results deal with those recently reported by Ibrahim et al [ 49 ]. The authors observed the disruption of the RPE barrier due to increased MMP2 metalloproteinase activity, following high BMP4 concentration.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, our group suggested that circulating BMP4 but not BMP2 or local retinal BMP4 is implicated in the pathogenesis of neovascular AMD. This conclusion was confirmed by demonstrating that BMP4 but not BMP2 interrupted the RPE barrier function, induced RPE migration and increased MMPs’ activity in RPE [ 80 ].…”
Section: Bmp and Diabetic Retinopathymentioning
confidence: 83%
“…Collectively, we are suggesting the presence of a differential impact of BMPs affecting retinal-blood barriers, with BMP2 dysregulation affecting mostly the inner barrier [ 54 , 72 ], and circulating BMP4 dysregulation affecting mostly the outer barrier [ 80 ] ( Figure 2 ). Retinal levels of BMP4 were detected by RNase protection assays in both non-diabetic RPE from human donors and ARPE-19 cells.…”
Section: Bmp and Diabetic Retinopathymentioning
confidence: 99%
“…Effects of CoCl 2 on barrier function of ARPE-19 were evaluated by monitoring changes in overall impedance (Z; ohms (Ω)). Normalized Z was recorded by Electric Cell-substrate Impedance Sensing (ECIS ® Zθ (theta)) biosensor technology (Applied Biophysics Inc) as previously described [ 22 ]. Briefly, a 96-wells arrays (96W20idf PET, Applied Biophysics Inc) were coated with 50 µL of 100 µM cysteine for 30 min followed by coating with 50 µL of 0.02% gelatin (Sigma; G1393) for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…ARPE-19 cells were stained with zonula occludens (ZO)-1 antibody according to our previous procedure [ 22 ]. Briefly, ARPE-19 cells were fixed in paraformaldehyde (4%, 10 min) followed by one-hour blockage in 0.2% gelatin in 0.3% tritonX-PBS.…”
Section: Methodsmentioning
confidence: 99%